Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Children's exposure to brominated flame retardants in the home: The TESIE study - Kate Hoffman; Xuening Tang; Ellen M. Cooper; Stephanie C. Hammel; Andreas Sjodin; Allison L. Phillips; Thomas F. Webster; Heather M. Stapleton (Environmental Pollution, 2024)

Distribution, hosts and long-term decline in abundance of the Patagonian lamprey inferred from diet assessment of albatrosses - Richard A. Phillips; Claire M. Waluda; Allison K. Miller (Reviews in Fish Biology and Fisheries, 2023)
Knowledge of lampreys during their marine phase is limited, and for the southern hemisphere species was gleaned from their predators (albatrosses) in the 1970s. Taking advantage of new methodologies and long-term data on predator diet and distributions, we infer diverse aspects of lamprey distribution and ecology. DNA analyses indicated that albatrosses at South Georgia prey on Patagonian lamprey Geotria macrostoma , originating from Argentina. Their core pelagic distribution when free swimming appears to be the Antarctic Polar Frontal zone (APFZ), and not South Georgia waters as assumed previously. If so, the APFZ would be the first known hotspot in abundance of an anadromous lamprey in oceanic waters. We could not identify a teleost fish that would be a likely host. Instead, we infer that the lamprey may prey on baleen whales, based on comparison of stable isotope ratios in lamprey with candidate host species, timing of appearance in albatross diets coincident with whale migrations, and circumstantial evidence (unexplained scarring recorded during the whaling era). We suggest that the lamprey do not tolerate cold Antarctic waters, and detach from southerly-migrating whales at the thermal boundary of the APFZ, where they become accessible to albatrosses in surface waters. Given strong evidence that relative importance of prey in seabird diets reflects availability in foraging areas, the steep decrease in the annual consumption of lamprey by albatrosses at South Georgia from > 550 tonnes in 1975–1976 and 1986, to very low levels in most years since 2012, is likely to indicate a major population decrease. Despite our unconventional means of assessing the population trend, there is a compelling case for listing of Patagonian lamprey at least as Near threatened by the International Union for the Conservation of Nature, and an urgent need to better understand anthropogenic threats in Argentina.

Characterizing azobenzene disperse dyes and related compounds in house dust and their correlations with other organic contaminant classes - Kirsten E. Overdahl; Christopher D. Kassotis; Kate Hoffman; Gordon J. Getzinger; Allison Phillips; Stephanie Hammel; Heather M. Stapleton; P. Lee Ferguson (Environmental Pollution, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Persistent autism-relevant behavioral phenotype and social neuropeptide alterations in female mice offspring induced by maternal transfer of PBDE congeners in the commercial mixture DE-71 - Elena V. Kozlova; Matthew C. Valdez; Maximillian E. Denys; Anthony E. Bishay; Julia M. Krum; Kayhon M. Rabbani; Valeria Carrillo; Gwendolyn M. Gonzalez; Gregory Lampel; Jasmin D. Tran; Brigitte M. Vazquez; Laura M. Anchondo; et al. (Archives of Toxicology, 2022)
Polybrominated diphenyl ethers (PBDEs) are ubiquitous persistent organic pollutants (POPs) that are known neuroendocrine disrupting chemicals with adverse neurodevelopmental effects. PBDEs may act as risk factors for autism spectrum disorders (ASD), characterized by abnormal psychosocial functioning, although direct evidence is currently lacking. Using a translational exposure model, we tested the hypothesis that maternal transfer of a commercial mixture of PBDEs, DE-71, produces ASD-relevant behavioral and neurochemical deficits in female offspring. C57Bl6/N mouse dams (F0) were exposed to DE-71 via oral administration of 0 (VEH/CON), 0.1 (L-DE-71) or 0.4 (H-DE-71) mg/kg bw/d from 3 wk prior to gestation through end of lactation. Mass spectrometry analysis indicated in utero and lactational transfer of PBDEs (in ppb) to F1 female offspring brain tissue at postnatal day (PND) 15 which was reduced by PND 110. Neurobehavioral testing of social novelty preference (SNP) and social recognition memory (SRM) revealed that adult L-DE-71 F1 offspring display deficient short- and long-term SRM, in the absence of reduced sociability, and increased repetitive behavior. These effects were concomitant with reduced olfactory discrimination of social odors. Additionally, L-DE-71 exposure also altered short-term novel object recognition memory but not anxiety or depressive-like behavior. Moreover, F1 L-DE-71 displayed downregulated mRNA transcripts for oxytocin ( Oxt ) in the bed nucleus of the stria terminalis (BNST) and supraoptic nucleus, and vasopressin ( Avp ) in the BNST and upregulated Avp1ar in BNST, and Oxtr in the paraventricular nucleus. Our work demonstrates that developmental PBDE exposure produces ASD-relevant neurochemical, olfactory processing and behavioral phenotypes that may result from early neurodevelopmental reprogramming within central social and memory networks.

Correction to: Responses of Lotus corniculatus to environmental change. 4: Root carbohydrate levels at defoliation and regrowth climatic conditions are major drivers of phenolic content and forage quality - Phillip Morris; Eunice B. Carter; Barbara Hauck; John-Wayne Hughes; Gordon Allison; Michael K. Theodorou (Planta, 2021)

Correction to: Responses of Lotus corniculatus to environmental change 3: The sensitivity of phenolic accumulation to growth temperature and light intensity and effects on tissue digestibility - Phillip Morris; Eunice B. Carter; Barbara Hauck; Alexandra Lanot; Michael K. Theodorou; Gordon Allison (Planta, 2021)

Responses of Lotus corniculatus to environmental change. 4: Root carbohydrate levels at defoliation and regrowth climatic conditions are major drivers of phenolic content and forage quality - Phillip Morris; Eunice B. Carter; Barbara Hauck; John-Wayne Hughes; Gordon Allison; Michael K. Theodorou (Planta, 2021)

Responses of Lotus corniculatus to environmental change 3: The sensitivity of phenolic accumulation to growth temperature and light intensity and effects on tissue digestibility - Phillip Morris; Eunice B. Carter; Barbara Hauck; Alexandra Lanot; Michael K. Theodorou; Gordon Allison (Planta, 2021)

Initial Outcomes of an Online Continuing Education Series Focused on Post-treatment Cancer Survivorship Care - Allison Harvey; Yuqing Zhang; Serena Phillips; Rhea Suarez; Laura Dekle; Aubrey Villalobos; Mandi L. Pratt-Chapman (Journal of Cancer Education, 2020)

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

Feasibility of Singlet Analysis for Ligand Binding Assays: a Retrospective Examination of Data Generated Using the Gyrolab Platform - Tracey H. Clark; Phillip D. Yates; Allison Given Chunyk; Alison P. Joyce; Aidong Wu; Petar Pop-Damkov; Yiqun Zhang; Elizabeth A. Dreher; Laurie A. Tylaska; Jo-Ann A. Wentland; Kathleen B. Pelletier; Lindsay E. King; et al. (The AAPS Journal, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Short-term decline of a Bahamian patch reef coral community: Rainbow Gardens Reef 1991–2004 - Eric Pante; Allison King; Phillip Dustan (Hydrobiologia, 2008)

Temporary alteration of local social structure in a threatened population of Cuban iguanas ( Cyclura nubila ) - Allison Alberts; Jeffrey Lemm; Andrew Perry; Lisa Morici; John Phillips (Behavioral Ecology and Sociobiology, 2002)